Improving material selection in shopping centres through a parametric life cycle embodied flow and material cost analysis model. (September 2022) - Weththasinghe, K.K.; Stephan, A.; Francis, V.; Tiwari, P.
Abstract: Shopping centres are significant built assets and part of the urban fabric in most developed economies. Yet very few studies have conducted a life cycle assessment of shopping centres, despite them using significant amounts of energy and resources throughout their life cycle. This paper presents a parametric model that quantifies the life cycle embodied flow (LCEF) and material cost (LCMC) of Australian shopping centres to inform material selection. Different combinations of building materials and assemblies are identified with minimum LCEF and LCMC for 13 different shop categories typical in shopping centres. The parametric model is used to simulate a case study centre which tests and analyses over 8820 scenarios and delivers benchmark values for the LCEF and LCMC of shopping centres. It shows that a typical centre using concrete and steel, average embodied flow intensities are 14.2 GJ/m 2 and 830 kgCO2 e/m 2 . It further demonstrates recurrent embodied flow, which is currently disregarded, is significant and represents up to 56% of the LCEF of a shopping centre over a period of 50 years. Results show that specific assembly combinations could achieve up to 32% LCEF reductions while saving up to 17% on material costs. Foundations and roof structure are identified as the most crucial of building elements for reducing embodied flow in the centre structure. This paper contributes to the embodied environmental impact assessment efforts and the energy-cost nexus by facilitating the appraisal and demonstrating broader societal impacts in making the built environment more economically and environmentally sustainable. Highlights: The model quantifies life cycle (LC) embodied environmental flows and cost of shopping centres. LC embodied energy (LCEE), GHG emissions and cost intensities for 3 shop categories within shopping centres are proposed. Average LCEE of a shopping centre using steel and concrete is 14 GJ/m 2 of which 56% are recurrent. Specific assembly combinations could achieve up to 32% LCEE and 17% cost reductions. Foundation and roof structure are the most critical assemblies for reducing embodied flows.